Multi-Level Marketing (MLM) Law According to the Fatwa of the Lajnah Daimah - Lalu Arcane Banjaran Sari (JURNAL PENDIDIKAN IPS, 2025)
This article examines the perspective of the Lajnah Daimah (Permanent Committee for Scholarly Research and Fatwa) regarding the legal status of Multi-Level Marketing (MLM) within the framework of Islamic Shariah. MLM is a controversial business model in Indonesia, often criticized for its resemblance to Ponzi schemes and its potential violation of key Islamic economic principles, such as riba (usury) and gharar (excessive uncertainty). Fatwa No. 22935 issued by the Lajnah Daimah explicitly declares MLM to be impermissible (haram), citing its emphasis on commission-based earnings over genuine product value, as well as its inherent elements of riba and gharar. This study provides a critical analysis of the fatwa and its implications for MLM practices in Indonesia, emphasizing the necessity of adhering to Shariah-compliant principles in business activities.